2007
DOI: 10.1038/modpathol.3800789
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive phosphorylation of the FOXO1A transcription factor as a prognostic variable in gastric cancer

Abstract: Increased phosphorylation of FOXO1A, a FOXO transcription factor, has been implicated in several human cancers; however, it has not been studied in the gastric cancer to date. To determine the status of pFOXO1A expression in human gastric cancers and to determine its relationship with other tumor-associated proteins, we performed immunohistochemical staining on tissue array slides containing 272 human gastric carcinoma specimens. In non-neoplastic gastric mucosa, the expression of pFOXO1A was observed primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to demonstrate the correlation between FOXO1 and chemoresistance in gastric cancer cells. We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…To the best of our knowledge, this is the first study to demonstrate the correlation between FOXO1 and chemoresistance in gastric cancer cells. We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…For example, VCAM-1, MMP-9 and uPA were up-regulated in gastric cancer and closely related to the metastasis, [17][18][19] while FKHR and connexin43 were down-regulated in gastric cancer. 20,21 Some of the dysregulated proteins were reported in other cancers but not in gastric cancer. For example, Pax-2 was up-regulated in renal cell cancer 22 and WT1 was down-regulated in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signalling pathway has emerged as a central mitogenic pathway in various types of mammalian cancer (Zbuk & Eng 2007) and there is amble evidence for a direct correlation between PI3K/Akt activation and FOXO inactivation in cancers (Kim et al 2007, Yip et al 2008.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%